Communication Patterns of the Qadariyah Naqsabandiyah Tarekat in Gawan Tradition in Mlagen Rembang - Ida Ariyani (UIN Salatiga, 2021)
This study aims to explore the unique traditions among the people of the qadariyah naqsabandiyah tarekat, Mlagen village, Pamotan sub-district, Rembang district, Central Java. Descriptive research method with the phenomenology. The interview technique used purposive sampling, interview by selecting sources in accordance with the direction of the study. The researcher did not select samples randomly, but actually looked for samples that matched the criteria. The results showed that gawan has indirectly become a tradition for the community. They will come to the kyai carrying gawan. The community will get a reward in the form of a level increase. As a tradition, if it is not carried out, the community will be embarrassed and embarrassed by itself. So that limitations and status as a poor family does not become a barrier for the community to improve the quality of worship.